Ubiquitous and gene-specific regulatory 5' sequences in a sea urchin histone DNA clone coding for histone protein variants. - Busslinger, M (1980)
The DNA sequences of the entire structural H4, H3, H2A and H2B genes and of their 5' flanking regions have been determined in the histone DNA clone h19 of the sea urchin Psammechinus miliaris. In clone h19 the polarity of transcription and the relative arrangement of the histone genes is identical to that in clone h22 of the same species. The histone proteins encoded by h19 DNA differ in their primary structure from those encoded by clone h22 and have been compared to histone protein sequences of other sea urchin species as well as other eukaryotes. A comparative analysis of the 5' flanking DNA sequences of the structural histone genes in both clones revealed four ubiquitous sequence motifs; a pentameric element GATCC, followed at short distance by the Hogness box GTATAAATAG, a conserved sequence PyCATTCPu, in or near which the 5' ends of the mRNAs map in h22 DNA and lastly a sequence A, containing the initiation codon. These sequences are also found, sometimes in modified version, in front of other eukaryotic genes transcribed by polymerase II. When prelude sequences of isocoding histone genes in clone h19 and h22 are compared areas of homology are seen to extend beyond the ubiquitous sequence motifs towards the divergent AT-rich spacer and terminate between approximately 140 and 240 nucleotides away from the structural gene. These prelude regions contain quite large conservative sequence blocks which are specific for each type of histone genes.